Platinum(II) complexes bearing bulky Schiff base ligands anchored onto mesoporous SBA‐15 supports as efficient catalysts for hydrosilylation. (10th April 2019) - Huo, Yingpeng; Hu, Jiwen; Lin, Shudong; Ju, Xingming; Wei, Yanlong; Huang, Zhenzhu; Hu, Yangfei; Tu, Yuanyuan
Abstract : Reported herein is an easy‐to‐prepare novel heterogeneous catalyst of platinum complexes bearing binary ligands of bidentate naphthalenolimine and cyclo‐1, 5‐octadiene that are anchored onto mesoporous silica SBA‐15. The presence of the binary ligands not only stabilized the platinum, but also enabled the platinum atoms to form nanoclusters with diameters of ca 1 nm, and led to high platinum loading (8.69 wt%). Moreover, the platinum catalyst exhibited high catalytic activity towards hydrosilylation of terminal alkenes and styrene with silanes under mild and solvent‐free conditions, with excellent regioselectivity. Abstract : A novel heterogeneous catalyst of platinum complexes bearing binary ligands of bidentate naphthalenolimine and cyclo‐1, 5‐octadiene was facilely prepared and fully characterized. The catalyst mediated hydrosilylation between olefins and trimethoxyl silane with excellent efficiency and regioselectivity.